Treating Mucocele in Pediatric Patients Using a Diode Laser: Three Case Reports - Sara M. Bagher; Ayman M. Sulimany; Martin Kaplan; Cheen Y. Loo (MDPI AG, 2018)
A mucocele is the most common minor salivary gland disease and among the most common biopsied oral lesions in pediatric patients. Clinically, a mucocele appears as a round well-circumscribed painless swelling ranging from deep blue to mucosa alike in color. Mucoceles rarely resolve on their own and surgical removal under local anesthesia is required in most cases. Different treatment options are described in the literature, including cryosurgery, intra-lesion injection of corticosteroid, micro-marsupialization and conventional surgical removal using a scalpel, and laser ablation. Therefore, the goal of this paper was to report three cases of mucocele removal in pediatric patients using a diode laser with a one-month follow-up. Mucoceles were removed by a pediatric dentist using a diode laser with a wavelength of 930 nm in continuous mode and a power setting of 1.8 Watts. In all cases, no bleeding occurred during or after the procedure and there was no need for suturing. On clinical examination during the one-month follow-up, in all three cases there was minimal or no scarring, minimal post-operative discomfort or pain, and no recurrence. Diode lasers provide an effective, rapid, simple, bloodless and well accepted procedure for treating mucocele in pediatric patients. Minimal post-operative discomfort and scarring was reported by all the three patients.